Epidemiological aspects of human visceral Leishmaniasis in the State of Piauí, Brazil (2007-2017) - Ferreira, Henrique Rafael Pontes (2021)
Background: Visceral leishmaniasis presents considerable expansion in urban centers in state of Piauí, its occurrence is marked by successive records of outbreaks. Objective: to analyze the reported cases of human visceral leishmaniasis in Piauí, between the years 2007 to 2017. Methods: The data were obtained from Notifiable Diseases Information System (Sinan-Datasus), variables were analyzed according to the Sinan registry. Results: 2,447 cases were reported, of which 2,265 autochthonous cases (92.56%). The conclusive diagnosis was made in 86.6% of the cases. The year with the highest record (283 cases) was 2014, also the annual lethality rate was 14.1%. Positive cases were registered in residents of 183 municipalities (81.7%). The capital Teresina presents the highest number of cases in residents (734, 30%) and notification (1,859, 75,97%). Male (66.30%) were the most affected and individuals under 10 years old (43.44%). Regarding education, the classification “does not apply” (39.84%) was the most prevalent, as well as race / brown color (88.27%) and the urban residential area (67.63%). Conclusion: Epidemiological assay, provides knowledge about the real epidemiological situation in state of Piauí, such as profile characterization, frequency of cases occurrence, assisting in actions for control and eradication of the disease in the state.